Study Of Adsorption Of Acid Violet 7 Dye Using Magnetic Adsorbent Prepared From Onion Peel - Sahul Hamid, Nur Fauzana (Universiti Sains Malaysia, 2018)
Magnetized porous biomass is an eco-friendly detoxification material which is highly efficient when used to remove dye and heavy metals from aqueous solutions. The adsorption of acid violet 7 (AV7) dye onto magnetic onion peel adsorbent (MOA) were investigated in a batch process. Onion peel (OP) undergoes magnetic process, where the OP was soaked into 1.0 mol/L Iron(III) chloride hexahydrate solution and stirred for eight hours to prepared MOA. The physical and chemical properties of MOA was investigated using Fourier transform infrared spectroscopy (FTIR). The MOA contained of metal oxide group, Si-O-Si group, C-C bending and benzene functional group. The effect of initial dye concentration (20-150mg/L), agitation time (0-60 minutes), adsorbent dosage (0.2-1.5 g) and shaker speed (50-300 rpm) were also evaluated through. The obtained equilibrium data for MB dye was best fitted by Langmuir model with monolayer adsorption capacity of 3.03 mg/g. Meanwhile, the kinetics data was best represented by the pseudo first-order model.